IMF Survey, Volume 31, Issue 16. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2002)
George T. Abed, a Palestinian and a Jordanian national, took over this summer as Director of the IMF's Middle Eastern Department. In his distinguished 20-year career at the IMF, he has worked on the Middle East and on fiscal policy issues worldwide. Outside the IMF, he taught at the University of California, Berkeley, and managed a development assistance foundation in Geneva, Switzerland. Laura Wallace spoke with him about the region's prospects amid political tensions and difficult economic challenges. Besides modernizing the state and liberalizing the region's economy, he stressed the paramount importance of democracy, human development, and attention to social needs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet